2018
DOI: 10.1177/1076029618790696
|View full text |Cite
|
Sign up to set email alerts
|

Application of High-Throughput Sequencing in the Diagnosis of Inherited Thrombocytopenia

Abstract: Inherited thrombocytopenia is a group of hereditary diseases with a reduction in platelet count as the main clinical manifestation. Clinically, there is an urgent need for a convenient and rapid diagnosis method. We introduced a high-throughput, next-generation sequencing (NGS) platform into the routine diagnosis of patients with unexplained thrombocytopenia and analyzed the gene sequencing results to evaluate the value of NGS technology in the screening and diagnosis of inherited thrombocytopenia. From a coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Different HTS studies for diagnostics of BPD have been published but for this review, we have only focussed on the studies that have used the guidelines for variant classification as formulated by the American College of Medical Genetics (ACMG) in 2015 [10]. Figure 2 provides an overview of the diagnostic rates obtained in these studies that however differ in terms of used HTS methods (TS or WES), studied pathologies (platelet disorders, coagulation disorders and bleeding of unknown etiology) and the number of genes and patients included [11][12][13][14][15][16][17][18][19][20][21]. In addition, these studies have used different inclusion criteria ranging from the selection of only patients with a known or suspected etiology (studies with typically high diagnostic rates) to patients with bleeding of unknown etiology and normal laboratory parameters (studies with very low diagnostic rates).…”
Section: Hts Technologies Used For Bpd Diagnosticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different HTS studies for diagnostics of BPD have been published but for this review, we have only focussed on the studies that have used the guidelines for variant classification as formulated by the American College of Medical Genetics (ACMG) in 2015 [10]. Figure 2 provides an overview of the diagnostic rates obtained in these studies that however differ in terms of used HTS methods (TS or WES), studied pathologies (platelet disorders, coagulation disorders and bleeding of unknown etiology) and the number of genes and patients included [11][12][13][14][15][16][17][18][19][20][21]. In addition, these studies have used different inclusion criteria ranging from the selection of only patients with a known or suspected etiology (studies with typically high diagnostic rates) to patients with bleeding of unknown etiology and normal laboratory parameters (studies with very low diagnostic rates).…”
Section: Hts Technologies Used For Bpd Diagnosticsmentioning
confidence: 99%
“…Other HTS studies have also reported variants in more than one gene but without further specifications if these had a clinical impact for the patient or family [11,[14][15][16][17][18]20]. Such examples of mostly digenic inheritance have recently also been documented in case reports.…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…The spread of next-generation sequencing (NGS) greatly contributed to the unraveling of the genetic basis of several forms of IPD, and thus immediately became a significant diagnostic tool in the field. Using a small amount of blood with minor risk of pre-analytical artifacts, it can provide patients with a highly accurate diagnosis [4][5][6][7][66][67][68][69][70][71][72]. As it becomes cheaper to perform, it is not inconceivable that NGS could become the standard above other diagnostic techniques.…”
Section: Current Diagnostic Tools For Ipdsmentioning
confidence: 99%
“…We read with interest the article by Wang et al recently published in Clinical and Applied Thrombosis/Hemostasis . 1 Here, the authors have evaluated the role of high-throughput sequencing in 43 apparently familial cases of thrombocytopenia using Drachman 2 review algorithm.…”
mentioning
confidence: 99%